Fatores preditivos para a ocorrência de pólipos endometriais em mulheres na pós-menopausa - Dias, Flávia Neves Bueloni [UNESP]; Dias, Daniel Spadoto [UNESP]; Nahás Neto, Jorge [UNESP]; Nahás, Eliana Aguiar Petri [UNESP] (FapUNIFESP (SciELO), 2014)
PURPOSE: To evaluate the predictive clinical factors for the development of endometrial polyps in postmenopausal women. METHODS: Observational cohort study with postmenopausal women who had been at a public university hospital. Clinical, anthropometrical, laboratorial, and ultrasonographic data of 132 patients with a histopathological diagnosis of endometrial polyps and 264 women without endometrial alterations (control) were compared in order to evaluate the predictive factors of endometrial polyps. Women with amenorrhea ≥12 months and ≥45 years of age were included in the study at a proportion of 1 case for 2 controls. The Student’s t-, χ2, and logistic regression tests were used for statistical analysis – odds ratio (OR). RESULTS: Patients with endometrial polyps were older and had been in menopause for a longer time compared to control (p<0.0001). The percentage of obese women with polyps (72.0%) was higher compared to the Control Group (39%; p<0.0001). The measurement of waist circumference was superior among patients with polyps (p=0.0001). We observed a higher incidence of diabetes, hypertension and dyslipidemia in patients with endometrial polyps (p<0.0001). According to the US National Cholesterol Education Program/Adult Treatment Panel III (NCEP/ATP III) criteria, 48.5% of women with polyps and 33.3% of the Control Group were classified as having metabolic syndrome (p=0.004). Analysis of risk for endometrial polyps formation showed higher chances of occurrence of the disorder in patients with: BMI≥25 kg/m² (OR=4.6; 95%CI 2.1–10.0); glucose ≥100 mg/dL (OR=2.8; 95%CI 1.3–5.9); dyslipidemia (OR=7.0; 95%CI 3.7–13.3); diabetes (OR=2.5; 95%CI 1.0–6.3), and metabolic syndrome (OR=2.7; 95%CI 1.1–6.4) compared to the Control Group. CONCLUSION: In postmenopausal women, obesity, dyslipidemia, hyperglycemia and presence of metabolic syndrome were predictive factors for the development of endometrial polyps.

OBJETIVO: Avaliar os fatores clínicos preditivos para o desenvolvimento dos pólipos endometriais em mulheres na pós-menopausa. MÉTODOS: Estudo de coorte observacional com mulheres na pós-menopausa, que haviam sido atendidas em hospital público universitário. Dados clínicos, antropométricos, laboratoriais e ultrassonográficos de 132 pacientes com diagnóstico anatomopatológico de pólipo endometrial e de 264 mulheres sem alterações endometriais (controle) foram comparados para avaliar os fatores preditivos do pólipo endometrial. Foram incluídas no estudo mulheres com amenorreia ≥12 meses e idade ≥45 anos, em uma proporção de 1 caso para 2 controles. Para a análise estatística, foram empregados os testes t de Student, χ2 e regressão logística — odds ratio (OR). RESULTADOS: As pacientes com pólipo endometrial apresentaram idade mais avançada e maior tempo de menopausa quando comparadas ao controle (p<0,0001). A porcentagem de mulheres obesas com pólipo (72,0%) foi superior à do Grupo Controle (39%; p<0,0001). A medida da circunferência da cintura foi superior entre as pacientes com pólipo (p=0,0001). Observou-se uma incidência de diabetes, hipertensão e dislipidemias mais elevada nas pacientes com pólipo endometrial (p<0,0001). De acordo com os critérios do US National Cholesterol Education Program/ Adult Treatment Panel III (NCEP/ATP III), 48,5% das mulheres com pólipo e 33,3% do Grupo Controle foram classificadas como portadoras de síndrome metabólica (p=0,004). Em relação ao Grupo Controle, apresentaram maior chance de desenvolvimento de pólipo endometrial as pacientes com: IMC≥25 kg/m2 (OR=4,6; IC95% 2,1–10,0); glicose ≥100 mg/dL (OR=2,8; IC95% 1,3–5,9); dislipidemia (OR=7,0; IC95% 3,7–13,3); diabetes (OR=2,5; IC95% 1,0–6,3) e síndrome metabólica (OR=2,7; IC95% 1,1–6,4). CONCLUSÃO: Em mulheres na pós-menopausa, obesidade, dislipidemia, hiperglicemia e presença de síndrome metabólica foram fatores preditivos para o desenvolvimento de pólipo endometrial.
Predictive factors for occurrence of endometrial polyps in postmenopausal women
Keywords: Endometrium; Risk factors; Menopause; Polyps; Metabolic syndrome X; Endométrio; Fatores de risco; Menopausa; Pólipos; Síndrome X metabólica